2011
DOI: 10.1007/s00436-011-2443-z
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of ribosomal protein S29, a deltamethrin resistance associated gene from Culex pipiens pallens

Abstract: The 40S ribosomal protein S29 (RPS29) was shown differentially expressed in deltamethrin (DM)-susceptible and resistant Culex pipiens pallens previously. Here, we cloned RPS29 from this mosquito. An open reading frame (ORF) of 171 bp was found to encode a putative protein with 56 amino acid residues, which shares more than 90% identities with other mosquito RPS29 genes. Moreover, quantitative real-time PCR analysis demonstrated that the transcriptional level of RPS29 was significantly up-regulated both in DM-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Ribosomal protein RPS29 was found to be associated with DM resistance in our previous study [14]. To investigate the mechanism, TAP was used to identify RPS29-interacting paterners.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ribosomal protein RPS29 was found to be associated with DM resistance in our previous study [14]. To investigate the mechanism, TAP was used to identify RPS29-interacting paterners.…”
Section: Discussionmentioning
confidence: 95%
“…Studies indicated that human RPS29 has extra-ribosomal functions as an apoptosis inducer and RNase [15], [16], but despite this, insect RPS29 remains poorly characterized. In our previous study, it had been identified that RPS29 is involved in DM resistance of mosquito [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were incubated with the transfection mixture for 4 h, and the transfection medium was replaced with 2 mL normal medium. After additional 24 h incubation, wells were then treated with various concentrations of deltamethrin (final concentrations, 0, 10 0.5 , 10 1.0 , 10 1.5 , and 10 2.0 μg/mL; Sun et al 2011). After another 48 h, 10 μL of CCK-8 solution were added to each well, and the plates were detected at 450 nm using a microplate reader after additional 4 h incubation.…”
Section: Methodsmentioning
confidence: 99%
“…C. pipiens mücadelesinde özellikle organofosfat temelli kimyasallar ve böcek büyüme inhibitörleri yaygın bir şekilde kullanılmaktadır. Fakat bu kimyasalların çevre ve insan sağlığı üzerindeki yan etkisi ve zararlıların uzun vade de bu kimyasallara karşı direnç geliştirmesi gibi kaygıları da beraberinde getirmektedir (Sun et al, 2011;Azizoğlu ve ark., 2012;Azizoğlu, 2014;Benelli et al, 2014;Lees et al, 2014). Bu kaygılardan dolayı doğal ortamla daha uyumlu, insan ve çevre sağlığı açısından daha güvenli mücadele tekniklerinin geliştirilmesi her geçen gün daha da önem kazanmaktadır.…”
Section: Introductionunclassified